Hospital training survival tips from seniors: a virtual experience sharing with students, local and international strategic partners / Wong Yuet Yen … [et al.] - Wong, Yuet Yen; Mohd Najib, Mohd Nadzri; Othman, Nursyuhadah; Ibrahim, Nurul Alyaa; Muhsain, Siti Nur Fadzilah (UiTM Global @ Office of International Affairs, 2024)
The Hospital Training Surviving Tips from the Seniors, a brainchild of the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Bertam Campus, Pulau Pinang, has been an annual event since 2018. The primary aim of the programme is to empower Semester Four Diploma in Pharmacy students who are about to embark on their ten months of hospital training. This initiative provides them with the knowledge, skills, and work ethics necessary to successfully complete their industrial training, which is a requirement for the Diploma in Pharmacy degree.